Adapting the psychological mediation framework for cisgender and transgender sexual minorities in Jamaica: Implications from latent versus observed variable approaches to sexual stigma. (January 2020) - Logie, Carmen H.; Lacombe-Duncan, Ashley; Wang, Ying; Levermore, Kandasi; Jones, Nicolette; Ellis, Tyrone; Bryan, Nicolette; Grace, Daniel
Abstract: Rationale: Sexual minorities' mental health disparities are produced in larger contexts of sexual stigma. There is limited understanding of pathways between sexual stigma dimensions (e.g., enacted, perceived, internalized), psychological processes, and depression. Objective: We aimed to test the psychological mediation framework among transgender and cisgender sexual minorities in Kingston, Montego Bay, and Ocho Rios, Jamaica. Methods: We conducted structural equation modeling using maximum likelihood estimation to examine direct and indirect pathways from sexual stigma to recent (past 2-week) depressive symptoms via mediators of resilient coping, social support quantity, and empowerment, and the moderation effect of social support quality. Results: Model 1 used a latent sexual stigma construct (indicators: enacted, perceived, and internalized stigma dimensions). Model 2 examined sexual stigma dimensions (enacted, perceived, internalized) as observed variables. Among participants (n=871; mean age: 25.5, SD: 5.4), 90.82% reported recent depressive symptoms. Both models fit the data well. In Model 1, the sexual stigma latent construct had a significant direct effect on depressive symptoms; social support quantity and resilient coping were partial mediators. In Model 2, enacted sexual stigma had a significant direct effect on depressive symptoms. Internalized sexual stigma had a significant indirect effect via social support quantity, resilient coping, and empowerment. Perceived sexual stigma had an indirect effect on depressive symptoms via empowerment. Social support quality moderated the relationship between: internalized stigma and empowerment, empowerment and resilient coping, social support quantity and resilient coping, and resilient coping and depressive symptoms. Conclusion: Findings suggest the importance of considering the synergistic effect of multiple sexual stigma dimensions on depression; exploring different sexual stigma dimensions to inform tailored stigma reduction and stigma coping interventions; andaddressing coping (e.g., resilience), social isolation (e.g., social support quantity/quality), and cognitive (e.g., empowerment) factors to mitigate the impacts of sexual stigma on depression among sexual minorities. Highlights: Research examining pathways from sexual stigma dimensions to depression is limited. Applied the psychological mediation framework with sexual minorities in Jamaica. Tested a latent sexual stigma construct and sexual stigma dimensions separately. Sexual stigma reduced social support and resilient coping to increase depression. Multiple approaches to sexual stigma measurement can inform interventions.